Oropharyngeal rhinosporidiosis in a migrant worker - A delayed presentation - Shailendra, S.; Prepageran, Narayanan (Malaysian Medical Association, 2008)
Rhinosporidiosis is a chronic granulomatous disease caused by an aquatic protistan parasite in the class of Mesomycetozoea, that is endemic in India and the subcontinent3,4. This is a case report of a rhinosporidiosis presenting in an individual from Myanmar, whom had been working in Malaysia for the past four years. The disease is characterized by the appearance of polypoidal, friable growths that contain numerous spore filled cysts that stain with PAS staining. This disease is rarely seen in Malaysians due to the extensive urbanization in Kuala Lumpur, however the increasing numbers of migrant workers in Malaysia today necessitates an increasing awareness in clinicians of the possibility of these conditions.